Racism and the Empathy for Pain on Our Skin - Forgiarini, Matteo; Gallucci, Marcello; Maravita, Angelo (Frontiers in Psychology, 2011)
Empathy is a critical function regulating human social life. In particular, empathy for pain is a source of deep emotional feelings and a strong trigger of pro-social behavior. We investigated the existence of a racial bias in the emotional reaction to other people’s pain and its link with implicit racist biases. Measuring participants’ physiological arousal, we found that Caucasian observers reacted to pain suffered by African people significantly less than to pain of Caucasian people. The reduced reaction to the pain of African individuals was also correlated with the observers’ individual implicit race bias. The role of others’ race in moderating empathic reactions is a crucial clue for understanding to what extent social interactions, and possibly integration, may be influenced by deeply rooted automatic and uncontrollable responses.